2002
DOI: 10.1128/jcm.40.11.4056-4059.2002
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation by 16S rRNA PCR of the COBAS AMPLICOR CT/NG Test for Diagnosis of Neisseria gonorrhoeae Infection in a Low-Prevalence Population

Abstract: The COBAS AMPLICOR CT/NG test is widely used for the diagnosis of Neisseria gonorrhoeae infection using genital swabs or urine samples. Although highly specific, cross-reactivity occurs with some nonpathogenic strains of Neisseria and Lactobacillus species. In low-prevalence populations, even highly specific assays may require confirmatory testing of positive results. We assessed the positive predictive value (PPV) of this test in a low-prevalence (0.5%) setting. Genital and urine specimens testing positive us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 23 publications
4
34
0
1
Order By: Relevance
“…Therefore, if the rate of test positivity in the population is 1.0%, then one-half of the observed positive results may be false-positive results, providing a positive predictive value of only 50%. When testing urogenital specimens in a low prevalence (0.5%) Canadian population, Diemert et al 72 found that the specificity of the Amplicor N. gonorrhoeae PCR assay was 98.7%, whereas the positive predictive value was only 31.3%. Thus, if positive results were issued for this Canadian population without supplementary testing, then close to 70% of positive results issued would in fact be false-positive results.…”
Section: Overall Impact Of Cross-reaction On Naat Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, if the rate of test positivity in the population is 1.0%, then one-half of the observed positive results may be false-positive results, providing a positive predictive value of only 50%. When testing urogenital specimens in a low prevalence (0.5%) Canadian population, Diemert et al 72 found that the specificity of the Amplicor N. gonorrhoeae PCR assay was 98.7%, whereas the positive predictive value was only 31.3%. Thus, if positive results were issued for this Canadian population without supplementary testing, then close to 70% of positive results issued would in fact be false-positive results.…”
Section: Overall Impact Of Cross-reaction On Naat Performancementioning
confidence: 99%
“…Notably, numerous studies conducted worldwide have shown positive predictive values for the Amplicor PCR assay on urogenital specimens below the 90% CDC threshold. 23,55,72,88,89 Increasing the positive result cutoff of the Amplicor assay will increase the positive predictive value of the test. This is because commensal Neisseria strains cross-reacting with the Amplicor assay may generally be at a low concentration or may contain minor base variations with the Amplicor PCR oligonucleotides.…”
Section: Roche Cobas Amplicormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, susceptibility test can be performed (25). For some authors, in areas where the N. gonorrhoeae prevalence is low, the culture is preferred over testing gene amplification (22). Other authors did not observe differences in sensitivity and specificity kits depending on the prevalence (23).…”
Section: N Gonorrhoeae and Molecular Biologymentioning
confidence: 99%
“…It is well recognised that some men with N gonorrhoeae are asymptomatic 2 and would be missed if the microorganism was not tested for, and Horner and Taylor-Robinson 22 advocate testing for both, but acknowledge the increased risk of falsepositives not only because it is a low-prevalence population 23 but also because some NAATs can detect commensal Neisseria species. [24][25][26] (2) As for (1) but examine and only undertake a Gram-stained urethral smear for those with a discharge. (3) As for (2) but include a leucocyte esterase test on those without a discharge.…”
Section: Clinical Role Of Testing For Urethritis In Asymptomatic Menmentioning
confidence: 99%